2001
DOI: 10.1097/00005768-200109000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Delta efficiencies of running and cycling

Abstract: The way of loading and the difference in metabolic intensity can be excluded as causes for the observed difference in delta efficiency between running and cycling. It is suggested that a different contribution in the metabolic load attributable to muscular activity of the arms and/or trunk that does not directly contribute to the work needed to overcome the amount of applied external load may be a relevant factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 20 publications
5
35
1
1
Order By: Relevance
“…Indeed, for some species the cost of incline running differs by as much as 150% from that predicted based on a constant efficiency of performing mechanical work against gravity. Furthermore, delta efficiencies calculated for incline running are often much greater (Taylor et al, 1972;Bijker et al, 2001) (this study) than the maximum efficiency of approximately 25% expected for skeletal muscle. These findings suggest that delta efficiency is likely a poor indicator of muscle efficiency during incline running.…”
Section: Delta Efficiency and Its Biological Relevancementioning
confidence: 62%
See 1 more Smart Citation
“…Indeed, for some species the cost of incline running differs by as much as 150% from that predicted based on a constant efficiency of performing mechanical work against gravity. Furthermore, delta efficiencies calculated for incline running are often much greater (Taylor et al, 1972;Bijker et al, 2001) (this study) than the maximum efficiency of approximately 25% expected for skeletal muscle. These findings suggest that delta efficiency is likely a poor indicator of muscle efficiency during incline running.…”
Section: Delta Efficiency and Its Biological Relevancementioning
confidence: 62%
“…Measures of delta efficiency (increase in gravitational mechanical energy divided by the increase in metabolic energy consumption) in uphill running are often greater than the maximum known efficiency of skeletal muscle (Taylor et al, 1972;Bijker et al, 2001), suggesting that some of the functions requiring energy on the level require less energy when running uphill. Developing hypotheses to explain the metabolic cost of running uphill has been hampered by the lack of information on the energy consumption of individual muscles.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the mean cycling D efficiency was 25%. Results from previous studies (Asmussen and Bonde-Petersen 1974;Suzuki 1979;Coyle et al 1992;Bijker et al 2001) have also shown that the D efficiency of cycling is indeed less than the efficiency of concentric exercise.…”
Section: Discussionmentioning
confidence: 85%
“…The D efficiency during running is significantly greater than that during cycling (Zacks 1973;Asmussen and Bonde-Petersen 1974;Bijker et al 2001). Furthermore, the D efficiency of running is also much greater than the muscle efficiency, which is estimated to have a maximal value of 29% (Cavanagh and Kram 1985).…”
Section: Introductionmentioning
confidence: 91%
“…Asmussen and Bonde-Petersen [2] also reported about the AE of walking and running using a similar technique according to Lloyd and Zacks [1]. Bijker et al [3] compared the delta efficiency of running with that of a bicycle ergometer exercise. Furthermore, the AE of running was compared between adults and children [4], and the effect of footwear (Japanese wooden clogs) on the AE of walking was also evaluated [5].…”
Section: Introductionmentioning
confidence: 99%